Molecular Communication for Coordinated Seed and Fruit Development: What Can We Learn from Auxin and Sugars? - Robert, Hélène S (International journal of molecular sciences, 2019)
Seed development in flowering plants is a critical part of plant life for successful reproduction. The formation of viable seeds requires the synchronous growth and development of the fruit and the three seed structures: the embryo, the endosperm, the seed coat. Molecular communication between these tissues is crucial to coordinate these developmental processes. The phytohormone auxin is a significant player in embryo, seed and fruit development. Its regulated local biosynthesis and its cell-to-cell transport capacity make of auxin the perfect candidate as a signaling molecule to coordinate the growth and development of the embryo, endosperm, seed and fruit. Moreover, newly formed seeds need nutrients and form new carbon sink, generating high sugar flow from vegetative tissues to the seeds. This review will discuss how auxin and sugars may be considered as signaling molecules to coordinate seed and fruit development.
Keywords: Signal Transduction; ovoce; Sugars; Indoleacetic Acids; cukry; vývoj rostlin; Plant Development; kyseliny indoloctové; signální transdukce; Seeds; Fruit; semena rostlinná